USM “IS IN A LEAGUE OF ITS OWN”, CHOICE OF GOLD MEDALLIST’S FAMILY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, November 2015 – Universiti Sains Malaysia (USM) has been the main choice for the family of the Chancellor’s Gold Medal recipient in the recent USM 52 Convocation, Yiauw Diing Sheng, 23, for higher tertiary education.